Make A Match Model on Students' Critical Thinking Ability About Fractional Numbers Class V UPTD SD Negeri 122337 Pematang Siantar - Novriyanti Ardani Easter Simanjuntak; Asister Fernando Siagian; Esti Sirait (International Journal of Integrated Science and Technology, 2023)
This research aims to determine whether there is an influence of the Contextual Teaching and Learning Model on the critical thinking abilities of fifth grade students at UPTD SD Negeri 122337 Pematang Siantar FY 2023/2024. The method in this research is a quantitative experimental method whose research design is Pre-experimental type one group. pretest-posttest. Conducted in October 2023, the population of all students at UPTD SD Negeri 122337 Pematang Siantar and a sample of 22 students consisting of 11 female students and 11 male students were used, namely purposing sampling with two research variables: the dependent variable (x) in the form of increase critical thinking skills, as well as the independent variable (y) in the form of a make a match model , a learning concept where students learn while playing using students matching pairs of cards on a fun topic. Data collection techniques are test techniques with validity tests, reliability tests, gain normality tests (n-gain). The test results using the Ngain technique with the help of the SPSS version 21 program, based on the calculation results obtained a mean of 0.71, with an effectiveness of 0.71 ≥ 0.7 which is included in the high category. All independent variables have a significant influence on the dependent variable. So it can be concluded that there is an influence of the make a match mode on the critical thinking abilities of class V students at UPTD SD Negeri 122337 Pematang Siantar FY 2023/2024.